2022
DOI: 10.1039/d2ra05782d
|View full text |Cite
|
Sign up to set email alerts
|

Polycationic doping of the LATP ceramic electrolyte for Li-ion batteries

Abstract: The tetravalent cations with similar sizes (Zr4+, Hf4+) supress the Ti4+ reduction while the bulky divalent cations (Ca2+, Sr2+) promote it even at relatively low concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Similar-sized tetravalent cations (Zr 4+ , Hf 4+ ) appear to be suppressing the Ti 4+ reduction, whereas large divalent cations (Ca 2+ , Sr 2+ ) appear to be promoting it even at low concentrations. Doping of Mg 2+ showed improvement in the Ti 4+ reduction tolerance; however, it demonstrated a detrimental effect on the conductivity after contact with Li metal [ 119 ]. Stegmaier et al conducted further research on the substitution of Mg 2+ in LATP and found that the Mg 2+ did not bleed heavily into the adjacent crystalline grain domains, which made it a suitable dopant for interfacial engineering.…”
Section: Solid-state Electrolytesmentioning
confidence: 99%
“…Similar-sized tetravalent cations (Zr 4+ , Hf 4+ ) appear to be suppressing the Ti 4+ reduction, whereas large divalent cations (Ca 2+ , Sr 2+ ) appear to be promoting it even at low concentrations. Doping of Mg 2+ showed improvement in the Ti 4+ reduction tolerance; however, it demonstrated a detrimental effect on the conductivity after contact with Li metal [ 119 ]. Stegmaier et al conducted further research on the substitution of Mg 2+ in LATP and found that the Mg 2+ did not bleed heavily into the adjacent crystalline grain domains, which made it a suitable dopant for interfacial engineering.…”
Section: Solid-state Electrolytesmentioning
confidence: 99%
“…In this work, we aimed to rationally investigate LiPON SE dopants that can best enhance the ionic conductivity of this SE while preserving a high electrical resistance, and carried out this investigation by performing density functional theory (DFT) calculations. We hypothesized that using a tetravalent metal (TM) for doping, which has been demonstrated with only a couple of elements, 19,20 may enhance the ionic conductivity of LiPON since TM substitution has been indicated to break the tetrahedral oxygen bonds in PO 4 , and widen the Li migration channel. We rst modeled the amorphized pristine LiPON and LiPONs doped with tetravalent cations (TM-LiPONs) to predict the metallicity, cell volumes, and thermal stability levels of the TM-LiPONs compared to those of the undoped LiPON system.…”
Section: Introductionmentioning
confidence: 99%